Mengurangi Nyeri Persalinan dengan Teknik Birthing Ball - Irawati, Ayu; Susianti, Susianti; Haryono, Iranita (Jurnal Bidan Cerdas, 2019)
Pain during labor is caused by the first stage of labor in which contractions cause dilation and thinning of the cervix and uterine ischemia due to contraction of the myometrial arteries. These contractions cause the opening of the cervix to begin labor. Various attempts are made to reduce labor pain, both pharmacologically and non-pharmacological. The non-pharmacological method applied is a distraction with birth balls. The research aims to prove the effectiveness of the use of birthing ball on the reduction of labor pain in the first stage of labor in the active phase. This study used an experimental research design with a pretest-posttest control group design. The research sample was 20 maternity mothers at the Lompoe Health Center, who received treatment and 20 people as control samples. It applied the purposive sampling technique. The instrument of observation was the pain scale using the Faces Pain Rating Scale. Data processing using the Wilcoxon-test to determine the effect of the treatment given. Based on the results of the bivariate analysis showed that the p-value is <0,001. In conclusion, there is an influence of using the birthing ball to reduce the level of pain in the first stage of labor in the active mother.